Accident cost ratio of bodily injury in railway construction projects / Nik Nur Khairunnisa Nik Mohd Ainul Azman ... [et al.] - Nik Nur Khairunnisa Nik Mohd Ainul Azman, Nik Mohd Ainul Azman; Asmalia, Che Ahmad; Mohmad, Mohd Derus; Izatul Farrita, Mohd Kamar (Universiti Teknologi MARA, Perak, 2018)
Accidents may harm any part of the body and may lead to minor injury or even fatalities. The effects of bodily injury may incur substantial direct costs and indirect costs to companies. The applications of existing accident costs ratios seem to be unsatisfactory for rail infrastructure project due to its unique accident situation and work environment. The purpose of the paper is to determine the ratio of direct costs to indirect costs for bodily injury in railway construction projects. A total of 70 accident cases between years 2010-2017 occurred in the railway construction projects were examined. The findings of the study may offer useful insight for safety practitioners in the estimation of direct and indirect costs for bodily injury accident costs on future railway construction projects.